From porphyrin benzylphosphoramidate conjugates to the catalytic hydrogenation of 5,10,15,20-tetrakis(pentafluorophenyl)porphyrin - Marcos C. de Souza; Leandro F. Pedrosa; Géssica S. Cazagrande; Vitor F. Ferreira; Maria G. P. M. S. Neves; José A. S. Cavaleiro (Beilstein Journal of Organic Chemistry, 2014)
Three new porphyrin aminoalkyl dibenzylphosphoramidates were synthesized by nucleophilic aromatic substitution of one p-fluorine atom of 5,10,15,20-tetrakis(pentafluorophenyl)porphyrin (TPPF20) by primary aminoalkyl dibenzylphosphoramidates. The nucleophilic aromatic substitution was promoted by microwave irradiation in N-methyl-2-pyrrolidinone. Attempts to remove the benzyl groups of the phosphoramidate moiety by hydrogenolysis with 10% Pd/C led to the cleavage of the P–N bond and the reduction of the macrocycle to hydroporphyrin-type derivatives. The extent of the effect of the catalytic hydrogenation to TPPF20 with 10% Pd/C was then studied with a variety of solvents. The results showed that ethanol/DMF is the solvent of choice to produce chlorin TPCF20 and an ethanol/DMF/NEt3 mixture is more adequate to produce isobacteriochlorin (TPIF20).